Alcohol-impaired driving among adults—USA, 2014–2018. Issue 3 (5th November 2021) - Barry, Vaughn; Schumacher, Amy; Sauber-Schatz, Erin
Abstract : Introduction: Alcohol-impaired driving (AID) crashes accounted for 10 511 deaths in the USA in 2018, or 29% of all motor vehicle-related crash deaths. This study describes self-reported AID in the USA during 2014, 2016 and 2018 and determines AID-related demographic and behavioural characteristics. Methods: Data were from the nationally representative Behavioral Risk Factor Surveillance System. Adults were asked 'During the past 30 days, how many times have you driven when you have had perhaps too much to drink?' AID prevalence, episode counts and rates per 1000 population were estimated using annualised individual AID episodes and weighted survey population estimates. Results were stratified by characteristics including gender, binge drinking, seatbelt use and healthcare engagement. Results: Nationally, 1.7% of adults engaged in AID during the preceding 30 days in 2014, 2.1% in 2016 and 1.7% in 2018. Estimated annual number of AID episodes varied across year (2014: 111 million, 2016: 186 million, 2018: 147 million) and represented 3.7 million, 4.9 million and 4.0 million adults, respectively. Corresponding yearly episode rates (95% CIs) were 452 (412–492) in 2014, 741 (676–806) in 2016 and 574 (491–657) in 2018 per 1000 population. Among those reporting AID in 2018, 80% were men, 86% reported binge drinking, 47% did not always use seatbelts and 60% saw physicians for routine check-ups within the past year. Conclusions: Although AID episodes declined from 2016 to 2018, AID was still prevalent and more common among men and those who binge drink. Most reporting AID received routine healthcare. Proven AID-reducing strategies exist.